Aid effectiveness and programmatic effectiveness: a proposed framework for comparative evaluation of different aid interventions in a particular health system - Hasibul Haque; Philip C. Hill; Robin Gauld (BMC, 2017)
Abstract Background Against a backdrop of changing concepts of aid effectiveness, development effectiveness, health systems strengthening, and increasing emphasis on impact evaluation, this article proposes a theory-driven impact evaluation framework to gauge the effect of aid effectiveness principles on programmatic outcomes of different aid funded programs in the health sector of a particular country. Methods The foundation and step-by-step process of implementing the framework are described. Results With empirical evidence from the field, the steps involve analysis of context, program designs, implementation mechanisms, outcomes, synthesis, and interpretation of findings through the programs' underlying program theories and interactions with the state context and health system. Conclusions The framework can be useful for comparatively evaluating different aid interventions both in fragile and non-fragile state contexts.